2014
DOI: 10.1140/epjb/e2014-50656-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport properties of a T-shaped double quantum dot system in the Coulomb blockade regime

Abstract: We investigate the thermoelectric properties of a T-shaped double quantum dot system described by a generalized Anderson Hamiltonian. The system's electrical conduction (G) and the fundamental thermoelectric parameters such as the Seebeck coefficient (S) and the thermal conductivity (κ), along with the system's thermoelectric figure of merit (ZT) are numerically estimated based on a Green's function formalism that includes contributions up to the Hartree-Fock level. Our results account for finite onsite Coulom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
(47 reference statements)
1
16
0
1
Order By: Relevance
“…Numerous works are focused on exploring properties of the thermopower of single-molecule junctions. It was shown that the thermopower may be affected by molecular vibrations [11][12][13][14][15][16][17], by effects of molecular bridge geometry [18][19][20][21][22] by interactions between electrons participating in transport [23][24][25][26][27][28][29][30] and by photons [31]. Under certain conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works are focused on exploring properties of the thermopower of single-molecule junctions. It was shown that the thermopower may be affected by molecular vibrations [11][12][13][14][15][16][17], by effects of molecular bridge geometry [18][19][20][21][22] by interactions between electrons participating in transport [23][24][25][26][27][28][29][30] and by photons [31]. Under certain conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a double quantum dot system ZT ≃ 300 in the vicinity of a Fano resonance when we neglect the onsite Coulomb interaction within the system component quantum dots [7]. Such a high figure of merit corresponds to an ideal configuration of the molecular junction, however, even for more realistic situations ZT > 1 [7,8].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Here, G is the electronic electrical conductance, T is the average temperature of the considered system and κ is the thermal conductance which generally includes contributions from both electrons and phonons (κ el and κ ph , respectively). It was shown that thermoelectric properties of single-molecule junctions may be affected by dephasing/inelastic effects [12][13][14], by the molecular bridge geometry [15,16], by Coulomb interactions between elec-trons on the bridge [17][18][19][20][21][22], by molecular vibrations [23][24][25][26], and by quantum interference [27,34]. Among thermoelectric properties of single-molecule junctions one may separate out the thermoelectric figure of merit ZT which is directly responsible for the thermoelectric efficiency of the system [32].…”
Section: Introductionmentioning
confidence: 99%